2020
DOI: 10.1021/acs.analchem.9b05582
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical 3D Depth Profiling of Collagen Fibrils in Native Tendon

Abstract: Connective tissue displays a large compositional and structural complexity that involves multiple length scales. In particular, on the molecular and the nanometer level, the elementary processes that determine the biomechanics of collagen fibrils in connective tissues are still poorly understood. Here, we use atomic force microscopy (AFM) to determine the three-dimensional (3D) depth profiles of the local nanomechanical properties of collagen fibrils and their embedding interfibrillar matrix in native (unfixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Thus, overlap regions are thicker, stiffer, and dissipate less energy than gap regions. This tendency was similar to the one observed on thicker collagen samples . Bottom-effect corrections were applied to remove the influence of the rigidity support (∼50 GPa) on the elastic modulus measurements (see SI for details).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, overlap regions are thicker, stiffer, and dissipate less energy than gap regions. This tendency was similar to the one observed on thicker collagen samples . Bottom-effect corrections were applied to remove the influence of the rigidity support (∼50 GPa) on the elastic modulus measurements (see SI for details).…”
Section: Resultssupporting
confidence: 71%
“…This tendency was similar to the one observed on thicker collagen samples. 43 Bottom-effect corrections were applied 44 to remove the influence of the rigidity support (∼50 GPa) on the elastic modulus measurements (see SI for details). The values of the elastic modulus reported here were similar to data obtained from AFM-based force–distance curves on thicker collagen fibrils (∼100 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Nanoscale mechanical property mapping is one of the key achievements of atomic force microscopy (AFM). Nanomechanical mapping is applied to facilitate the development of or to improve the characterization of materials and interfaces. Nanomechanical measurements are widely used in mechanobiology to reveal how elastic and viscoelastic properties of proteins, cells, and the extracellular matrix influence biological processes. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible to estimate the Young's modulus of the sample at a desired indentation spot for various indentation depths. Previously released studies have shown that this approach can be applied to soft materials such as cells (Stuhn et al 2019), polymers (Dehnert and Magerle 2018), bacteria (Longo et al 2013), graphene oxide (Dehnert et al 2016) or collagen fibrils (Magerle et al 2020).…”
Section: Introductionmentioning
confidence: 99%